2021
DOI: 10.5772/intechopen.96023
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Their Role in Staphylococcus aureus Resistance and Virulence

Abstract: Staphylococcus aureus is a pathogen of great importance to clinical and veterinary medicine. Recently, there has been a growing interest in S. aureus extracellular vesicles (EVs) in the pathogenesis of this bacterium. Released by living cells into the extracellular milieu, EVs are membranous structures carrying macromolecules such as proteins, nucleic acids, and metabolites. These structures play several physiological roles and are, among others, considered a mechanism of intercellular communication within S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
(154 reference statements)
0
4
0
Order By: Relevance
“…5 ) as follows: (1) the structural integrity of the biofilm could be compromised through a loss of appropriate folding of scaffolding proteins like amyloid curli. (2) As the SMRwt peptide is capable of EV blockade in both viral infected cells and cancer cells, we postulated that it could similarly affect bacterial intercellular communication networking that is reliant upon EV transmission ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 ) as follows: (1) the structural integrity of the biofilm could be compromised through a loss of appropriate folding of scaffolding proteins like amyloid curli. (2) As the SMRwt peptide is capable of EV blockade in both viral infected cells and cancer cells, we postulated that it could similarly affect bacterial intercellular communication networking that is reliant upon EV transmission ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite the variations that were found, the EV core proteome still carries proteins that are linked to virulence (e.g., Ebps, Sbi), metabolism (e.g., Eno, PdhABCD), survival (e.g., FhuD), and resistance (FmtA, PBPs). Many of these elements are also found across several S. aureus strains [23,25] and may play active roles in the infection and pathogenesis of this bacterium. Interestingly, differences in protein abundance were observed when comparing growth phases in WC and EVs.…”
Section: Discussionmentioning
confidence: 99%
“…The study of EVs is an emerging field in medical and veterinary medicine of S. aureus since several reports have highlighted their contribution to cargo delivery, signaling, and cell-cell communication, contributing to physiological and pathological processes [23]. Indeed, S. aureus EVs carry several virulence factors (e.g., β-lactamases, toxins, adhesins) that exert essential functions, including the transfer of antibiotic resistance to susceptible bacteria, host cell death, immunomodulation, and exacerbation of inflammatory processes [8,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Microbe-derived EVs have emerged as an important novel research topic in the context of understanding the role of gut microbial communities in human health and disease. The first study of bEVs reported secreted bEVs produced by the Gram-negative bacteria Escherichia coli in cultures in 1966 [164], while EVs from Gram-positive bacteria was first published only in 2009, from Staphylococcus aureus [165]. The reason for the delayed discovery of vesicles from Gram-positive bacteria has been attributed to the thick PG cell wall of Gram-positive bacteria that was assumed to act as a barrier to their release [165].…”
Section: Bacterial Extracellular Vesiclesmentioning
confidence: 99%